IFPRI-Bangladesh "Using the BIHS Data to Support Agriculture, Nutrition, and Social Protection Policies in Bangladesh" - Ahmed, Akhter (2018)
IFPRI Country Representative for Bangladesh Dr. Akhter Ahmed presents panel data from IFPRI's Bangladesh Integrated Household Survey (BIHS) in New Delhi, India.